PENGARUH METODE PEMBELAJARAN EVERY ONE IS A TEACHER HERE TERHADAP PENINGKATAN KETERAMPILAN BERPIKIR KRITIS SISWA KELAS V PADA PEMBELAJARAN IPA DI SD - Sifa, Akromatus; Andriana, Encep; Syachruroji, A. (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2024)
Abstract: This research aims to determine the improvement of critical thinking skills through the application of the every one is a teacher here learning method for class V students in science learning at SDN Sindang Mandi. This research was conducted in six meetings, one pre-test, four lessons and one post-test. The subjects of this research were all class V of SDN Sindang Mandi. This research is experimental research and data collection techniques use tests and non-tests. This research's data analysis technique uses data from pre-test and post-test results and N-Gain to determine the increase in critical thinking skills in both classes. The research results showed an increase in students' critical thinking skills through the N-Gain test in the experimental class, with an average value of 0.6713 > 0.3493 in the control class. From these results it can be said that the every one is a teacher here method has a higher percentage of learning improvement than conventional methods in terms of critical thinking abilities.